An induced pluripotent stem cell line (TRNDi006-A) from a MPS IIIB patient carrying homozygous mutation of p.Glu153Lys in the NAGLU gene - Huang, Wei (Stem Cell Res, 2019)
Mucopolysaccharidosis type III B (MPS IIIB) is a lysosomal storage disorder caused by mutations in the NAGLU gene encoding N-acetylglucosaminidase. Here, we report the generation of a human induced pluripotent stem cell (iPSC) line from dermal fibroblasts of a MPS IIIB patient. The iPSC line has homozygous mutations of G > A transversion at nucleotide 457 of the NAGLU gene (457G > A), resulting in the substitution of lysine for glutamic acid at codon 153 (Glu153Lys). This iPSC line allows for the study of disease phenotypes and pathophysiology as well as disease modeling in human cells.